CTNI-61. CLINICAL EFFICACY AND PREDICTIVE BIOMARKERS OF ONC201 IN H3K27M-MUTANT DIFFUSE MIDLINE GLIOMA. (14th November 2022) - Kawakibi, Abed Rahman; Tarapore, Rohinton; Gardner, Sharon; Chi, Andrew; Kurz, Sylvia; Wen, Patrick Y; Arrillaga-Romany, Isabel; Batchelor, Tracy; Butowski, Nicholas; Sumrall, Ashley; Shonka, Nicole; Harrison, Rebecca; et al.
Abstract: Patients with H3K27M-mutated diffuse midline glioma (DMG) have no proven effective therapies beyond radiation. ONC201, a DRD2 antagonist and mitochondrial ClpP agonist, has shown promise in this population. Clinical and genetic variables associated with ONC201 response in H3K27M-mutant DMG continue to be investigated. A combined clinical and genetic study evaluated patients with H3K27M-DMG treated with single-agent ONC201 at the established phase 2 dose. Clinical outcomes of patients treated on two recently completed multi-site clinical studies (NCT03416530 and NCT03134131, n = 75) were compared with historical control data from patients with confirmed H3K27M-DMG (n = 391 total, n = 119 recurrent). Patients treated with ONC201 monotherapy following initial radiation, but prior to recurrence, demonstrated a median overall survival (OS) of 25.6 months from diagnosis and recurrent patients demonstrated a median OS of 16.2 months from recurrence, both of these more than doubling historical outcomes. Using a Cox model to correct for age, gender and tumor location, OS of ONC201-treated patients with H3K27M-mutant tumors remained significantly better than non-ONC201-treated historical controls (p = 0.0001). A survival and radiographic analysis based on tumor location, revealed stronger responses in thalamic patients. In patients with thalamic tumors treated after initial radiation (n = 16), median OS was not reached with median follow up of 22.1 months (historical control median OS of 12.5 months, n = 83, p = 0.0001). Significant correlations were found between baseline cerebral blood flow (CBF) on perfusion imaging and OS (Pearson's r = 0.75, p = 0.003) and between nrCBF and PFS (r = 0.77, p = 0.002). Baseline tumor sequencing from treated patients (n = 20) demonstrates EGFR mutation (n = 3) and high EGFR expression as a marker of resistance and improved response in tumors with MAPK-pathway alterations (n = 5). In conclusion, ONC201 demonstrates unprecedented clinical and radiographic efficacy in H3K27M-mutant DMG with outcomes enriched in patients with thalamic tumors, treatment prior to recurrence, MAPK-pathway alterations, and patients with relatively high CBF.